The Tax Revenue from Agriculture and Manufacturing Sectors in Lower Middle-Income Countries with Exchange Rate as a Moderating Variable - Destiny Wulandari; Suparna Wijaya (Ilomata International Journal of Tax and Accounting, 2023)
Middle-income trap triggers the middle-income countries to boost their economic growth. As tax revenue has causal relationship with economic growth, it is essential to conduct a study on how to improve tax revenue. Considering the potential of agriculture and manufacturing sectors in lower middle-income countries, particularly in East Asia and Pacific Regions one of which is Indonesia, this study aims to determine the effects of both sectors on tax revenue in the respective regions. This study uses exchange rate as moderating variable and foreign direct investment (FDI) as control variable. The utilization of the two variables becomes the novelty of this study since researches that uses the two variables have never been conducted. In addition, no references of former studies concerning the effects of the two sectors on tax revenue in lower middle-income countries found. The research is conducted from 2002 to 2019 by using panel data multiple linear regression analysis method. By using fixed effect model and ridge regression model, it is indicated that before the moderation is carried out, agriculture has a negative effect and manufacture has a positive effect on tax revenue. However, after the variables are moderated with exchange rate, the interaction of agriculture and exchange rate has positive effect on tax revenue, while the interaction of manufacture and exchange rate has negative effect on tax revenue. This study implies that to optimize a country's tax revenue, apart from focusing on optimizing agriculture or manufacture, exchange rate condition needs to be considered.